The evolution of the reform of the social sphere in the ideas of Jadidism - Xo‘shboqova Dilchehra Baxtiyor qizi (Peerian Journals Publishing, 2024)
In this article, the emergence of the Jadidism movement and the evolution of the reform of the social sphere in the ideas of Jadidism are studied
Keywords: Modernity; social sphere; reform; evolution